If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8s + -11 = -5 + 9s Reorder the terms: -11 + 8s = -5 + 9s Solving -11 + 8s = -5 + 9s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-9s' to each side of the equation. -11 + 8s + -9s = -5 + 9s + -9s Combine like terms: 8s + -9s = -1s -11 + -1s = -5 + 9s + -9s Combine like terms: 9s + -9s = 0 -11 + -1s = -5 + 0 -11 + -1s = -5 Add '11' to each side of the equation. -11 + 11 + -1s = -5 + 11 Combine like terms: -11 + 11 = 0 0 + -1s = -5 + 11 -1s = -5 + 11 Combine like terms: -5 + 11 = 6 -1s = 6 Divide each side by '-1'. s = -6 Simplifying s = -6
| 2(8n+3)=8n+3 | | 2p-13=-7+p | | 9x+16=x | | 4+6q=-(3q+3) | | 77-2x=16x+19 | | -7-7x=42-14x | | 46-4x=5x+11 | | 20x^4-24x^2+9x^2= | | -2x(x+3)=4x-3 | | 5x+13y=-17solvex | | -5(y+4)= | | 3(2x-1)=4x-9 | | -6x+14=-16 | | 7x-2(4x+8)=-13 | | 4x=98 | | 7(4.03)= | | 5x-11=4x-8 | | 3(x+21)= | | 5(98)= | | (2x+10)+(3x+39)=180 | | 3-(3*2-7)= | | -3(8+5)= | | (r+k+3)6= | | 3x-17-8x=3 | | 10x^2=25x | | 3/6=x-3/8 | | 4/6=x/24 | | x/15=3/4 | | 9p-15=15+4p | | 2(w-33)+5=3(w-1) | | m+4/7=2/3 | | 6y-16=-10+4y |